Income risk inequality: Evidence from Spanish administrative records - Manuel Arellano; Stéphane Bonhomme; Micole De Vera; Laura Hospido; Siqi Wei (Quantitative Economics, 2022)
In this paper, we use administrative data from the social security to study income dynamics and income risk inequality in Spain between 2005 and 2018. We construct individual measures of income risk as functions of past employment history, income, and demographics. Focusing on males, we document that income risk is highly unequal in Spain: More than half of the economy has close to perfect predictability of their income, while some face considerable uncertainty. Income risk is inversely related to income and age, and income risk inequality increases markedly in the recession. These findings are robust to a variety of specifications, including using neural networks for prediction and allowing for individual unobserved heterogeneity.
Keywords: D31; E24; E31; J31; 330; Spain; income dynamics; administrative data; income risk; inequality